Topography-mediated aboveground biomass (AGB) carbon storage in semiarid Patagonia: native forests and pine plantations at the landscape scale - Tatiana Alejandra Valfré-Giorello; Lisandro Agost; Georgina Conti; Carla Montero; Maria Elena Oneto; Daniel Roberto Pérez (Journal of Arid Environments, 2026)

Infectious spondylodiscitis: Epidemiology, diagnosis, microbiological findings, clinical features and outcomes in a 14-year retrospective study - Jacopo Conti; Nicholas Geremia; Stefano Di Bella; Fulvio Zadra; Verena Zerbato; Stella Babich; Venera Costantino; Manuela Di Santolo; Marina Busetti; Filippo Mearelli; Leonello Tacconi; Marco Francesco Maria Cavallaro; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose To describe the epidemiology, diagnosis, microbiological findings, clinical features, and outcomes of infectious spondylodiscitis (IS). Methods Retrospective analysis of 98 IS patients (2010–2023 - Trieste Hospital). Clinical, radiological, and microbiological data analysed, multivariate logistic regression assessed risk factors for poor outcomes. Results The incidence of IS was 3 cases per 100,000 inhabitants per year. Pyogenic infections accounted for 54% of cases, tuberculosis for 10%, while 35% remained of unknown etiology. Back pain (79%) and fever (72%) were the most common symptoms. Staphylococcus aureus was the most common pathogen, with 34 cases, representing 64% of pyogenic spondylodiscitis. Blood cultures were positive in 47% of pyogenic cases, 25% of all cases. PET/CT showed higher diagnostic utility (83%) than labeled leukocyte scintigraphy (54%). The lumbar spine was the most affected region (63%), followed by thoracic (25%) and cervical (12%). Neurosurgical biopsy showed a 33.3% positivity rate, while CT-guided biopsy yielded 22%. Cervical (OR 4.76) and thoracic (OR 3.89) involvement were associated with worse outcomes. Major complications included radicular nerve damage (51%), epidural/paravertebral abscesses (45%), endocarditis (14%), and a need for surgical intervention in 8%, with persistent neurological sequelae in 3%. Infection-related mortality rate was 6%. Conclusion S. aureus remains the leading pathogen in IS. Blood cultures play a key role, yielding positive in half of pyogenic cases. PET/CT surpassed leukocyte scintigraphy and improved MRI diagnostic accuracy. Lumbar involvement correlates with better outcomes, and open biopsy provides a higher diagnostic yield than percutaneous TC-guided biopsy. Empirical therapy is required in one-third of cases.

Thrust fault maturity and coseismic behavior: Insights from the 2022 Mw5.8 Adriatic offshore earthquake - Lorenzo Petracchini; Stefano Tavani; Marco Brandano; Eugenio Carminati; Claudio Chiarabba; Alessia Conti; Roberto Devoti; Paolo Galli; Mimmo Palano; Giuseppe Pezzo; Laura Scognamiglio; Elisa Tinti; et al. (Earth and Planetary Science Letters, 2025)

The Implementation of Decision Aids During Medical Consultations for Lung Cancer Patients: A Focus Group Within I3LUNG Project - Valeria Sebri; Patrizia Dorangricchia; Dario Monzani; Chiara Marzorati; Roberto Grasso; Lorenzo Conti; Giuseppe Lo Russo; Leonardo Provenzano; Andra Diana Dumitrascu; Gabriella Pravettoni (Journal of Cancer Education, 2025)
Lung cancer patients generally receive several information regarding their illness characteristics and available intervention. Therefore, patients can experience confusion, leading to anxiety and distress that might damage the relationship with physicians and treatment adherence. Literature showed that implementing decision aid tools during consultation can promote patients’ knowledge and awareness about lung cancer and available oncological intervention, improving a shared decision-making process. However, not all lung cancer patients always appreciate decision aids’ implementation. The present qualitative study explored patients’ opinions and preferences regarding the implementation of decision aids during medical consultation. Twenty-two lung cancer patients who have already attended medical consultations for lung cancer voluntarily participated in four online focus groups carried out between January 2023 and December 2024. A thematic analysis with a bottom-up approach highlighted three main themes: the typology and number of information that patients would have received, the relevance of patient-and-doctor relationship, and the effects of providing additional decision-making tools on patients’ emotions and preferences. Findings showed controversial opinions among patients, highlighting the relevance of personalized intervention tailored to patients’ preferences. Practical implications are given.

Salvage therapy of complicated Candida albicans spondylodiscitis with Rezafungin - Nina Grasselli Kmet; Roberto Luzzati; Jacopo Monticelli; Stella Babich; Jacopo Conti; Stefano Di Bella (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The involvement of bark canker fungal pathogens in cypress windbreak dieback in northern Tunisia - Azza Chtioui; Meriem Zouaoui Boutiti; Roberto Danti; Sara Barberini; Niccolò Conti; Arcangela Frascella; Ferid Abidi; Gianni Della Rocca (Fungal Biology, 2025)

Plant Growth-Promoting Yeasts (PGPYs) as a sustainable solution to mitigate salt-induced stress on zucchini plant growth - Chiara Ruspi; Debora Casagrande Pierantoni; Angela Conti; Roberto Scarponi; Laura Corte; Gianluigi Cardinali (Biology and Fertility of Soils, 2025)

Best practices, errors, and perspectives of half a century of plant translocation in Italy - Martina D'Agostino; Luigi Cao Pinna; Marta Carboni; Silvia Assini; Gianluigi Bacchetta; Fabrizio Bartolucci; Lisa Brancaleoni; Fabrizio Buldrini; Angelino Carta; Bruno Cerabolini; Roberta Maria Ceriani; Umberto Clementi; et al. (Conservation Biology, 2024)
Conservation translocations are becoming common conservation practice, so there is an increasing need to understand the drivers of plant translocation performance through reviews of cases at global and regional levels. The establishment of the Italian Database of Plant Translocation (IDPlanT) provides the opportunity to review the techniques used in 186 plant translocation cases performed in the last 50 years in the heart of the Mediterranean Biodiversity Hotspot. We described techniques and information available in IDPlanT and used these data to identify drivers of translocation outcomes. We tested the effect of 15 variables on survival of translocated propagules as of the last monitoring date with binomial logistic mixed‐effect models. Eleven variables significantly affected survival of transplants: life form, site protection, material source, number of source populations, propagation methods, propagule life stage, planting methods, habitat suitability assessment, site preparation, aftercare, and costs. The integration of vegetation studies in the selection of suitable planting sites significantly increased the success of translocation efforts. Although posttranslocation watering had a generally positive effect on translocation outcome, other aftercare techniques did not always increase transplant survival. Finally, we found that how funds were spent appeared to be more important than the actual amount spent. Plant translocations in Italy and in the Mediterranean area should account for the complexity of speciation, gene flow, and plant migrations that has led to local adaptations and has important implications for the choice and constitution of source material.

Altitudinal variation of microplastic abundance in lakeshore sediments from Italian lakes - Marco Parolini; Elena Perin; Beatrice De Felice; Stefano Gazzotti; Adriano Palazzi; Luca Conti; Eleonora Conterosito; Emanuela Rosio; Francesco Bruno; Valentina Gianotti; Roberto Cavallo (Environmental Science and Pollution Research, 2024)
Microplastic (MP) contamination represents an issue of global concern for both aquatic and terrestrial ecosystems, but only in recent years, the study of MPs has been focused on freshwaters. Several monitoring surveys have detected the presence of a wide array of MPs differing in size, shape, and polymer composition in rivers and lakes worldwide. Because of their role of sink for plastic particles, the abundance of MPs was investigated in waters, and deep and shoreline sediments from diverse lakes, confirming the ubiquity of this contamination. Although diverse factors, including those concerning anthropogenic activities and physical characteristics of lakes, have been supposed to affect MP abundances, very few studies have directly addressed these links. Thus, the aim of the present study was to explore the levels of MP contamination in mountain and subalpine lakes from Northern Italy. Fourteen lakes dislocated at different altitudes and characterized by dissimilar anthropic pressures were visited. Lakeshore sediments were collected close to the drift line to assess MPs contamination. Our results showed the presence of MPs in lakeshore sediments from all the lakes, with a mean (± standard deviation) expressed as MPs/Kg dry sediment accounting to 14.42 ± 13.31 (range 1.57–61.53), while expressed as MPs/m 2 , it was 176.07 ± 172.83 (range 25.00–666.67). The MP abundance measured for Garda Lake was significantly higher compared to all the other ones ( F 1,13 = 7.344; P < 0.001). The pattern of contamination was dominated by fibers in all the lakes, but they were the main contributors in mountain lakes. These findings showed that the MP abundance varied according to the altitude of the lakes, with higher levels measured in subalpine lakes located at low altitudes and surrounded by populated areas.

Mangrove individual tree detection based on the uncrewed aerial vehicle multispectral imagery - Priscila Almeida de Oliveira; Luis Américo Conti; Francisco Cordeiro Nascimento Neto; Roberto Lima Barcellos; Marília Cunha-Lignon (Remote Sensing Applications: Society and Environment, 2024)

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Vicia faba plants respond to oviposition by invasive Halyomorpha halys activating direct defences against offspring - Gabriele Rondoni; Valeria Bertoldi; Robert Malek; Khaled Djelouah; Chiaraluce Moretti; Roberto Buonaurio; Eric Conti (Journal of Pest Science, 2018)

Hospital admissions in Iran for cardiovascular and respiratory diseases attributed to the Middle Eastern Dust storms - Yuef Omidi Khaniabadi; Roberto Fanelli; Alessandra De Marco; Seyed Mohammad Daryanoosh; Itai Kloog; Philip K. Hopke; Gea Oliveri Conti; Margherita Ferrante; Mohammad Javad Mohammadi; Ali Akbar Babaei; Hassan Basiri; Gholamreza Goudarzi (Environmental Science and Pollution Research, 2017)

Plasma concentrations of efavirenz, darunavir/ritonavir and raltegravir in HIV-HCV-coinfected patients without liver cirrhosis in comparison with HIV-monoinfected patients - Leonardo Calza; Ilaria Danese; Vincenzo Colangeli; Roberto Manfredi; Eleonora Magistrelli; Gabriella Verucchi; Matteo Conti; Roberto Motta; Pierluigi Viale (Infectious Diseases, 2015)

Heterogeneous drug target expression as possible basis for different clinical and radiological response to the treatment of primary and metastatic renal cell carcinoma: suggestions from bench to bedside - Matteo Santoni; Daniele Santini; Francesco Massari; Alessandro Conti; Roberto Iacovelli; Luciano Burattini; Giampaolo Tortora; Massimo Falconi; Rodolfo Montironi; Stefano Cascinu (Cancer and Metastasis Reviews, 2014)

A study of NOAA particle flux sensitivity to solar activity and strategies to search for correlations among satellite data and earthquake phenomena - Cristiano Fidani; Roberto Battiston; William J. Burger; Livio Conti (International Journal of Remote Sensing, 2012)

Evaluation of Heavy Metals and Polycyclic Aromatic Hydrocarbons (PAHs) in Mullus barbatus from Sicily Channel and Risk-Based Consumption Limits - Gea Oliveri Conti; Chiara Copat; Caterina Ledda; Maria Fiore; Roberto Fallico; Salvatore Sciacca; Margherita Ferrante (Bulletin of Environmental Contamination and Toxicology, 2012)

An integrated GIS for sedimentological and geomorphological analysis of a lagoon environment. Barra de Cananéia inlet region, (Southeastern Brazil) - Luis Américo Conti; Carlos Alberto S. Araujo; Fernando S. Paolo; Roberto L. Barcellos; Marcelo Rodrigues; Michel M. Mahiques; Valdenir V. Furtado (Journal of Coastal Conservation, 2012)

Effects of the increase in neuronal fatty acids availability on food intake and satiety in mice - Roberto Coccurello; Antonio Caprioli; Sara Bellantuono; Francesca R. D’Amato; Roberto Conti; Fabio Giannessi; Franco Borsini; Anna Moles (Psychopharmacology, 2010)

Cytomorphological study on human submandibular gland following treatment with secretagogue drugs - Francesca Testa Riva; Roberto Puxeddu; Francesco Loy; Gabriele Conti; Alessandro Riva (Cell and Tissue Research, 2006)

Identification of QTLs for root characteristics in maize grown in hydroponics and analysis of their overlap with QTLs for grain yield in the field at two water regimes - Roberto Tuberosa; Maria Corinna Sanguineti; Pierangelo Landi; Marcella Michela Giuliani; Silvio Salvi; Sergio Conti (Plant Molecular Biology, 2002)